Use of fibrin sealant and tunica vaginalis flap in the repair of urethro-cutaneous fistulas: experience in a tertiary care centre - Kulkarni, Apoorva; Dikshit, Vishesh; Gupta, Abhaya; Kothari, Paras; Jayaswal, Shalika; Kekre, Geeta (International Surgery Journal, 2018)
Background: Urethro-cutaneous (UC) fistulas are one of the most common complications after hypospadias surgery. To repair a UC fistula, an experienced surgeon with vast knowledge in the field of hypospadias is essential. Various techniques of UC fistula repair have been described. We share our experience in the use of fibrin sealant and tunica vaginalis flap as intermediate cover in UC fistula repairs. Methods: Our objective was to evaluate the efficacy of fibrin sealant and tunica vaginalis flap in urethro-cutaneous fistula repair in those patients where dartos flap is not available. Total 40 patients were retrospectively evaluated and segregated into the fibrin sealant group and the tunica vaginalis flap group. All repairs had been done by the same surgeon with 6-0 polyglactin suture at least 6 months from the primary repair. The re-fistulation rate was noted in both the groups. Results: Re-fistulation rate was 20% for tunica vaginalis flap and 70% for fibrin sealant. The general re-fistulation rate with the use of dartos flap is 20-30% at our institute. Conclusions: We concluded that tunica vaginalis flap as intermediate cover gives good results in urethro-cutaneous fistula repair.